9 Identification of thirty novel loci for cardiovascular magnetic resonance derived aortic distensibility in the UK Biobank. (1st November 2021) - Fung, Kenneth; Biasiolli, Luca; Hann, Evan; Lukaschuk, Elena; Ramírez, Julia; Duijvenboden, Stefan van; Aung, Nay; Paiva, Jose M; Sanghvi, Mihir M; Thomson, Ross J; Lee, Aaron M; Piechnik, Stefan K; et al.
Abstract : Introduction: Cardiovascular magnetic resonance (CMR)-derived aortic distensibility (AoD) is a validated tool to measure arterial stiffness 1 . This local stiffness marker is an independent predictor of cardiovascular events and all-cause mortality 2 . Our knowledge of genes modulating aortic stiffness remains limited. We conducted genome-wide association studies (GWASs) for AoD in the ascending aorta (AA) and proximal descending aorta (PDA). Methods: 34, 039 UK Biobank (UKB) participants of European ancestry with transverse cine images of pulmonary trunk and right pulmonary artery acquired using a 1.5T CMR scanner were included. AoD is defined as the relative change in cross-sectional aorta area for a given change in central pulse pressure, they were either manually derived or processed through a developed automated algorithm 3 . GWASs were performed using linear mixed models 4 using ~7 million imputed variants adjusted for age, sex, height, weight, systolic blood pressure, aortic area segmentation method (manual/automated), imaging centre, genotype array, smoking, diabetes mellitus and top 10 principal components. Bioinformatic analyses were performed including investigation of trait pleiotropy. Polygenic risk scores (PRS) for AA and PDA were calculated using PRSice 5 and tested for association with major adverse cardiovascular events (MACE) in the UKB cohort without imaging data (n= 98, 559). Results and discussion: Variants at 18 independent loci for AA and 16 loci for PDA AoD were genome-wide significant, P < 5 × 10 −8 ( table 1 and figure 1 ) with four shared loci between the two phenotypes. The heritability for both AA and PDA AoD was ~27%, much higher than arterial stiffness index (6%) 6 but comparable to pulse wave velocity (36–40%) 7, 8 . We captured a modest percentage of the genetic variance for each trait (2.7% for AA; 2.1% for PDA). Several candidate genes are highlighted including ELN for both traits, with ISL1 and PCSK1 both involved in insulin regulation that may explain the interplay with diabetes 9, 10 . Variants at 13 loci were significant with blood pressure and/or coronary artery disease traits. We observed no significant difference in odds ratio for MACE between the top and bottom quintiles for each PRS. Conclusion: We identified 30 genetic loci providing new candidate genes for exploration of biological mechanism of AoDs. References: Nelson A, Worthley S, Cameron J, Willoughby S, Piantadosi C, Carbone A, Dundon B, Leung M, Hope S, Meredith I, Worthley M. Cardiovascular magnetic resonance-derived aortic distensibility: validation and observed regional differences in the elderly. Journal of Hypertension . 2009;27:535–542. Redheuil A, Wu CO, Kachenoura N, Ohyama Y, Yan RT, Bertoni AG, Hundley GW, Duprez DA, Jacobs DR, Daniels LB, Darwin C, Sibley C, Bluemke DA, Lima JAC. Proximal Aortic Distensibility Is an Independent Predictor of All-Cause Mortality and Incident CV Events. Journal of the American College of Cardiology . 2014;64:2619–2629. Biasiolli L, Hann E, Lukaschuk E, Carapella V, Paiva JM, Aung N, Rayner JJ, Werys K, Fung K, Puchta H, Sanghvi MM, Moon NO, Thomson RJ, Thomas KE, Robson MD, Grau V, Petersen SE, Neubauer S, Piechnik SK. Automated localization and quality control of the aorta in cine CMR can significantly accelerate processing of the UK Biobank population data. PLOS ONE . 2019;14:e0212272. Loh P-R, Tucker G, Bulik-Sullivan BK, Vilhjálmsson BJ, Finucane HK, Salem RM, Chasman DI, Ridker PM, Neale BM, Berger B, Patterson N, Price AL. Efficient Bayesian mixed-model analysis increases association power in large cohorts. Nature Genetics . 2015;47:284–290. Choi SW, O'Reilly PF. PRSice-2: Polygenic Risk Score software for biobank-scale data. Gigascience [Internet]. 2019 [cited 2020 Feb 4];8. Available from: https://academic.oup.com/gigascience/article/8/7/giz082/5532407 Fung K, Ramírez J, Warren HR, Aung N, Lee AM, Tzanis E, Petersen SE, Munroe PB. Genome-wide association study identifies loci for arterial stiffness index in 127, 121 UK Biobank participants. Scientific Reports . 2019;9:9143. Sayed-Tabatabaei FA, Van Rijn MJE, Schut AFC, Aulchenko YS, Croes EA, Zillikens MC, Pols HAP, Witteman JCM, Oostra BA, Van Duijn CM. Heritability of the function and structure of the arterial wall: findings of the Erasmus Rucphen Family (ERF) study. Stroke . 2005;36:2351–2356. Mitchell GF, DeStefano AL, Larson MG, Benjamin EJ, Chen M-HH, Vasan RS, Vita JA, Levy D. Heritability and a genome-wide linkage scan for arterial stiffness, wave reflection, and mean arterial pressure: The Framingham heart study. Circulation . 2005;112:194–199. Ediger BN, Du A, Liu J, Hunter CS, Walp ER, Schug J, Kaestner KH, Stein R, Stoffers DA, May CL. Islet-1 Is Essential for Pancreatic β-Cell Function. Diabetes . 2014;63:4206–4217. Stijnen P, Ramos-Molina B, O'Rahilly S, Creemers JWM. PCSK1 Mutations and Human Endocrinopathies: From Obesity to Gastrointestinal Disorders. Endocr Rev . 2016;37:347–371.